Filsafat Islam dan Model Pembelajaran di Era Artificial Intelligence: Analisis Epistemologis dan Etis - Zaka Vikryan (Universitas Majalengka, 2026)
The development of Artificial Intelligence (AI) has brought significant changes to various fields, including Islamic education. AI technology offers numerous opportunities, such as personalized learning, expanded access to educational resources, improved assessment efficiency, and the development of adaptive learning models tailored to students’ needs. However, the implementation of AI also raises various ethical concerns that require careful examination from the perspective of Islamic philosophy. This study aims to analyze the ethical implications of AI utilization in learning processes, formulate a conceptual framework of Islamic philosophy relevant to AI-based learning, and examine its implications for educators and Islamic educational policies. The study employs a qualitative approach using a library research method through the analysis of scholarly literature indexed in Google Scholar and published between 2023 and 2025. The findings indicate that the implementation of AI in Islamic education should be grounded in the principles of tawhid (divine unity), amanah (trustworthiness), justice, public welfare (maslahah), and the moral responsibility of human beings as khalifah (vicegerents) on earth. The ethical implications identified include the potential for students’ intellectual dependency, threats to academic integrity, algorithmic bias, and risks related to privacy and data security. A relevant Islamic philosophical framework is constructed through the integration of ontology, epistemology, and axiology, positioning revelation as the normative foundation, reason as a critical instrument, technology as a learning tool, and public welfare as the ultimate educational objective. Therefore, educators need adequate AI literacy, while educational institutions should formulate policies that integrate digital ethics, data protection, and the principles of maqaṣid al-syari‘ah to ensure that AI utilization contributes to the development of insan kamil (the holistic human being) in the digital era.